2004
DOI: 10.1677/joe.1.05802
|View full text |Cite
|
Sign up to set email alerts
|

The effects of steroidal estrogens in ACI rat mammary carcinogenesis: 17β-estradiol, 2-hydroxyestradiol, 4-hydroxyestradiol, 16α-hydroxyestradiol, and 4-hydroxyestrone

Abstract: Several investigators have suggested that certain hydroxylated metabolites of 17 -estradiol (E 2 ) are the proximate carcinogens that induce mammary carcinomas in estrogensensitive rodent models. The studies reported here were designed to examine the carcinogenic potential of different levels of E 2 and the effects of genotoxic metabolites of E 2 in an in vivo model sensitive to E 2 -induced mammary cancer. The potential induction of mammary tumors was determined in female ACI rats subcutaneously implanted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 33 publications
3
45
1
2
Order By: Relevance
“…A 50% incidence of mammary tumors in animals treated with E 2 (3mg) occurred at 16 weeks, whereas a 50% incidence in rats treated with the low dose of E 2 (1 mg) was noted at about 36 weeks. This dose dependency of the incidence of palpable mammary tumors is comparable to that reported earlier for ACI rats implanted with cholesterol pellets containing 1 or 3 mg E 2 (Turan, et al,2004). With the exeception of one rat treated with the high dose of E 2 and fed the clofibrate-containing diet, there were no detectable palpable mammary tumors before 15 weeks.…”
Section: Experiments 1-supporting
confidence: 87%
See 1 more Smart Citation
“…A 50% incidence of mammary tumors in animals treated with E 2 (3mg) occurred at 16 weeks, whereas a 50% incidence in rats treated with the low dose of E 2 (1 mg) was noted at about 36 weeks. This dose dependency of the incidence of palpable mammary tumors is comparable to that reported earlier for ACI rats implanted with cholesterol pellets containing 1 or 3 mg E 2 (Turan, et al,2004). With the exeception of one rat treated with the high dose of E 2 and fed the clofibrate-containing diet, there were no detectable palpable mammary tumors before 15 weeks.…”
Section: Experiments 1-supporting
confidence: 87%
“…26, 239-253. The failure of E2 to stimulate uterine growth in female ACI rats was expectet (e.g., Turan et al (2004); ).…”
Section: Tissue Wet Weights and Serum E 2 Levelsmentioning
confidence: 99%
“…However, El-Bayoumy and colleagues (32) reported that cholesterol epoxides and estrone-3,-4-quinone lack tumorigenic activity in the rat mammary gland. Treatment of pellets containing 2-OHE 2 , 4-OHE 2 , 16a-OHE 2 , or 4-OHE 1 failed to induce any significant mammary tumorigenesis compared with E 2 in the ACI rats (33). Therefore, the direct involvement of 4-OHE 2 or other metabolites of E 2 in the mammary carcinogenesis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, conflicting findings against the carcinogenic activity of catechol estrogens and their intermediates have been reported. Turan et al 13 demonstrated the lack of mammary gland carcinogenicity for 2-and 4-OHE 2 and 4-OHE 1 in the estrogen-sensitive female ACI rat. El-Bayoumy et al…”
mentioning
confidence: 99%